Transvaginal Resection of a Bladder Leiomyoma Misdiagnosed with a Vaginal Mass: A Case Report and Literature Review - Fu-Fen Yin; Ning Wang; You-Lin Wang; Xiao-Ning Bi; Xiao-Hui Xu; Yan-Kui Wang (Case Reports in Obstetrics and Gynecology)
Bladder leiomyoma is a rare benign tumor and it could be easily misdiagnosed with many other pelvic diseases, especially obstetrical and gynecological diseases; abdominal, laparoscopic, and transurethral resection of bladder leiomyoma have been reported. Herein, we present a case of bladder leiomyoma misdiagnosed with a vaginal mass preoperatively; the mass was isolated, enucleated from the bladder neck, and removed transvaginally; to the best of our knowledge, this is the first case of intramural leiomyoma of bladder neck that has been enucleated transvaginally only without cystotomy.